30th Annual Frontiers in Education Conference. Building on a Century of Progress in Engineering Education. Conference Proceedin
DOI: 10.1109/fie.2000.896588
|View full text |Cite
|
Sign up to set email alerts
|

Cross-functional teams used in computer science senior design capstone courses

Abstract: Traditionally, computer science curricula focus on teaching technical content, either ignoring the importance of interpersonal communication or relegating it to separate courses with no integration of communication and technical skills. Thus, students get little practice with communication of technical information and even less appreciation for its importance. For the past several years one of the computer science senior design courses at NC State University has emphasized teaming, process, and professional co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…They can be instructor-driven projects or support an internal or external client (e.g., [19]). In addition to technical focuses, they may also provide students with learning experiences related to professional conduct [20], code/version management [21] or collaboration/team work skills [22,23]. Hotaling et al [24] have shown that an interdisciplinary approach to PBL/EE, such as could be created via the use of some of the learning technologies described herein, was demonstrated to result in better "holistic performance in innovation, utility, analysis, proof of concept and communications skills."…”
Section: Experiential Educationmentioning
confidence: 99%
“…They can be instructor-driven projects or support an internal or external client (e.g., [19]). In addition to technical focuses, they may also provide students with learning experiences related to professional conduct [20], code/version management [21] or collaboration/team work skills [22,23]. Hotaling et al [24] have shown that an interdisciplinary approach to PBL/EE, such as could be created via the use of some of the learning technologies described herein, was demonstrated to result in better "holistic performance in innovation, utility, analysis, proof of concept and communications skills."…”
Section: Experiential Educationmentioning
confidence: 99%